Sebaceous Gland Heterotopia of the Esophagus: A Rare Incidental Finding During Upper Endoscopy - Samuel Ramos; Margaret-Anne Huntley; Eric Vargas; Jignesh Parikh; Vania Zayat (HCA Healthcare Journal of Medicine, 2026)
Esophageal heterotopic sebaceous glands (EHSG) are an extremely rare finding within the esophageal epithelium. These glands are typically benign, presenting as small, yellow-white plaques or lesions observed on endoscopy, often in the middle third of the esophagus. Esophageal heterotopic sebaceous glands are generally asymptomatic, and surveillance is not required. While their origin is unclear, proposed mechanisms include metaplastic transformation and congenital development. Recognition and histologic confirmation are essential to distinguish EHSG from other esophageal lesions and to avoid unnecessary interventions. We report the case of a 55-year-old man in whom multiple diminutive plaques were identified in the mid-esophagus during esophagogastroduodenoscopy (EGD) performed to evaluate persistent gastroesophageal reflux disease (GERD). Pathological examination revealed esophageal sebaceous gland heterotopia without associated malignancy or concerning features. We present an endoscopic image and a photomicrograph demonstrating the gross and histologic appearance of EHSG, respectively.